The Surau's Ethnopedagogy: Weaving Faith and Culture in Minangkabau - Fadri, Zainal; Prayoga, Andhika Gilang (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
This study examines the Surau education pattern in Minangkabau, Indonesia, as a response to the growing disconnect between youth and their cultural heritage amidst modernization. This research aims to re-document the Surau education pattern, analyze its historical and cultural aspects, and propose a revitalization model that adapts it to contemporary challenges. The study seeks to expand the paradigm of Islamic education by incorporating local cultural heritage and practices, recognizing the significance of regional traditions in shaping educational experiences within Islamic contexts. Employing a descriptive qualitative approach with an ethnopedagogical framework, this research utilizes in-depth interviews with traditional leaders, religious figures, youths, and community representatives, and participatory observation and documentation study. Data analysis was executed using thematic analysis techniques, focusing on educational patterns, values imparted, and their implications for youth's social preparedness. The findings reveal that Surau education implements a contextual and practical learning model, enabling students to gain theoretical knowledge of religion and practice these values through various social and cultural activities. The Surau is an effective educational arena for instilling honesty, responsibility, deliberation, and preserving Minangkabau cultural identity. Moreover, Surau education fosters resilient mental character and social skills that support students' adaptation within broader society. Surau education significantly contributes to the holistic life readiness of Minangkabau youth, establishing Surau as a traditional education model relevant to future development. This model significantly shapes a morally grounded, religious, and socially prepared younger generation. It positively impacts Islamic value-based community education and revitalizes Surau as a relevant spiritual and social learning space in contemporary society.